2005
DOI: 10.1007/s10899-005-3101-0
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol’s Effects on Video Lottery Terminal (VLT) Play Among Probable Pathological and Non-Pathological Gamblers

Abstract: This study tested whether alcohol increases behaviors associated with video lottery terminal (VLT) play, particularly among probable pathological gamblers. Forty-four regular VLT players were designated either probable pathological gamblers or non-pathological gamblers on the basis of scores on the South Oaks Gambling Screen (SOGS); [Lesieur & Blume (1997). American Journal of Psychiatry, 144, 1184-1188] Gamblers from each SOGS category were randomly assigned to either a moderately intoxicating alcohol dose or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
80
4
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(97 citation statements)
references
References 35 publications
9
80
4
3
Order By: Relevance
“…Previous findings suggest that alcohol may increase gambling by prolonging ongoing gambling sessions Kyngdon and Dickerson, 1999) and alcohol may have increased participants' gambling if they had had more time and money available to them. Moreover, in contrast to past studies (e.g., Ellery et al, 2005), in the present study gambling occurred in a ventilated smoking laboratory that was devoid of many of the contextual cues that might normally be associated with gambling and it is possible that certain alcohol effects on gambling behavior are context-specific. Alternatively, since previous investigations of alcohol effects on gambling did not systematically control for tobacco/nicotine use it is possible that uncontrolled tobacco use may have contributed to differences previously attributed to alcohol.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Previous findings suggest that alcohol may increase gambling by prolonging ongoing gambling sessions Kyngdon and Dickerson, 1999) and alcohol may have increased participants' gambling if they had had more time and money available to them. Moreover, in contrast to past studies (e.g., Ellery et al, 2005), in the present study gambling occurred in a ventilated smoking laboratory that was devoid of many of the contextual cues that might normally be associated with gambling and it is possible that certain alcohol effects on gambling behavior are context-specific. Alternatively, since previous investigations of alcohol effects on gambling did not systematically control for tobacco/nicotine use it is possible that uncontrolled tobacco use may have contributed to differences previously attributed to alcohol.…”
Section: Discussionmentioning
confidence: 71%
“…For example, Ellery et al (2005) reported that probable pathological gamblers who received alcohol gambled significantly longer using a video-lottery terminal (VLT) and engaged in more 'risky' wagering behaviors relative to those that received a non-alcoholic control drink. The effect of alcohol on risky wagering was recently replicated in a follow-up study (Ellery and Stewart, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Hingson et al 30 have estimated that in 2001 alone, more than 1700 college students aged 18 to 24 years died from alcohol-related injuries, more than 500,000 suffered unintentional injury, and more than 600,000 were assaulted by other students who were drinking. Alcohol intake also increases time spent gambling and the riskiness of bets made 31 and is a strong risk factor for suicide 32 and nonfatal injury. 33 Disinhibition 34 and impulsivity 35 are two of the most widely accepted mechanisms by which excessive alcohol consumption promotes risky behaviors, and both are particularly linked to binge and heavy drinking.…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol abuse has been linked to defective decision making and the development of gambling problems (Lesieur et al 1991;Ellery et al 2005;Maccallum and Blaszczynski 2002) and has been observed to precede the development of gambling problems (Ramirez et al 1983;Kausch 2003). A study with adolescents found that participants who were rated as high or moderately frequent drinkers in the previous year (had consumed alcohol on more than 12 days in the past year) were more likely to gamble compared to those rated as low or abstinent alcohol users who had used alcohol on less than 12 days in the previous year (Duhig et al 2007).…”
mentioning
confidence: 99%